The role of physiotherapy in a health maintenance strategy for retirees in Indonesia to support total defense - Faonaso Harefa; Yahdiana Harahap; Dian Andriani Ratna Dewi; R.M. Tjahya Nurrobi; Sutanto; Cecilia F. Harsono (Physical Therapy Journal of Indonesia, 2026)
Background: Retirement represents a critical transitional phase for members of the Indonesian military and civil servants, often accompanied by post-power syndrome and retirement depression, which adversely affect psychological stability, musculoskeletal function, and social participation. This study aimed to empirically analyze the effectiveness of physiotherapy interventions based on physical activity combined with psychosocial support in mitigating post power syndrome and retirement depression, while also assessing their alignment with the job demands-resources model and the successful aging theory. Methods: This study employed a quantitative analytical survey involving 200 retired Indonesian military personnel and civil servants (≥1 year post-retirement) selected through simple random sampling. Data were collected using structured Likert-scale questionnaires covering physiotherapy interventions, post-power syndrome symptoms, and mental health indicators. Validity and reliability were confirmed through pilot testing. Data were analyzed using structural equation modelling with partial least squares (SEM-PLS 4) to assess relationships and model fit through outer and inner model evaluations. Results: The results indicate that all constructs met the criteria for validity and reliability (outer loading > 0.70; AVE > 0.50; CR > 0.80; HTMT < 0.85). Physiotherapy interventions demonstrated a significant effect in reducing PPS (β = -0.62; t = 8.522; p < 0.001) and retirement depression (β = -0.67; t = 7.274; p < 0.001), with musculoskeletal function and physical activity engagement acting as significant partial mediators (t = 5.275; p < 0.001). These findings affirmed that integrated physiotherapy interventions enhance retirees’ physical resilience and psychosocial well-being, while also holding strategic relevance for national health policies and strengthening the role of retirees as supportive components within the national defense and security system. Conclusion: This research contributes to advancing physical and mental well-being among the elderly through integrated physiotherapy interventions; however, its cross-sectional design presents a limitation, suggesting future studies adopt longitudinal approaches with broader contextual variables.